Mikołaj Gogol w kontekście kulturowym epoki (na materiale opowiadania А. Połtorackiego „W Petersburgu”) - Romaszczenko, Ludmiła (Studia Rossica Posnaniensia, 2011)
In the article based on the story In Petersburg by Alexei Poltoratsky, N. Gogol's personality in the cultural context of Russian empire capital is considered. Special attention is paid to creative relations of N. Gogol with prominent cultural personalities of that time: Pushkin, Jukovsky, Delvig, Maximowich and others. Except that the author reconsiders some stereotypes of appraisals touching these historical persons.